Dissolution profiles of partially purified bromelain from pineapple cores [Ananas comosus (L.) Merr] encapsulated in glutaraldehyde-crosslinked chitosan - Siswati Setiasih, Hegi Adi Prabowo, Emil Budianto, Sumi Hudiyono (Journal of Applied Pharmaceutical Science, 2018)
To avoid degradation in the stomach, the proteolytic enzyme bromelain must be encapsulated in glutaraldehyde-crosslinked chitosan (CGF) hydrogels, which can maintain the activity of bromelain until it reaches the intestine. In this study, we isolated bromelain by using ammonium sulfate precipitation, dialysis, and anionic exchange chromatography with Diethylaminoethyl (DEAE)-cellulose resin. Bromelain fractions were collected from each purification step and specific activities were sequentially from increased in the crude enzyme, ammonium sulfate, dialysis, and DEAE chromatography fractions (fraction numbers 58–71), which have fractions of 23.90, 122.00, 125.48, and 195.20 U/mg, respectively. Bromelain fractions from the dialysis step were encapsulated in CGF matrixes by using a post-loading method. CGF hydrogels had a crosslinking degree of 84.37% and swelling ratio of 76.60%. The dissolution profiles of CGF-encapsulated bromelain were tested in artificial stomach fluid and intestinal environments, and bromelain encapsulation efficiency following the post-loading method was 96.29%. Interactions between the hydrogel and bromelain were limited to the hydrogen bonds, and the proteolytic activities of bromelain were maintained at 0.17 U/ml in the present artificial intestinal environment.
Keywords: Bromelain, purification, post-loading encapsulation, crosslinked chitosan, dissolution.